Structural Variations of Dust Acoustic Solitary Waves (DASWs) Propagating in an Inhomogeneous Plasma - Dehingia, Hirak Jyoti; Deka, P.N. (East European Journal of Physics, 2023)
This paper presents our theoretical investigations on the structural variations of dust acoustic solitary waves (DASWs) in inhomogeneous unmagnetized plasmas. To study the structural variations of DASWs, we have considered collisionless, hot isothermal, and Boltzmannean distribution for electrons-ions with negatively charged dust grains in weakly inhomogeneous plasmas. We have used the reductive perturbation technique (RPT) in the governing equations of plasmas, derived the modified Korteweg-de-Vries (m‑KdV) equation, and obtained the solitary wave solution. We have considered the appropriate stretched coordinates for space and time variables for the inhomogeneous plasma. This paper investigates the effects of dust particles on ion-acoustic solitary waves’ propagation in the inhomogeneous plasma model. We have also included the effect of inhomogeneity parameters on the soliton structures.